ESG and corporate governance: a systematic review - Ab Aziz, Noor Hidayah; Abdul Latif, Ahmed Razman; Osman, Mohammad Noor Hisham; Alshdaifat, Sajead (Global Academic Excellence, 2023)
In an era when organisations are under more significant pressure to balance operational effectiveness with ethical and environmental obligations, it is critical to comprehend the impact of environmental, social and governance (ESG) on corporate governance (CG). This review aims to synthesize the current body of literature, distinguishing significant themes, trends, and gaps to present a structured synthesis of this field. This research utilised the PRISMA framework. An advanced search strategy was performed using Scopus and Web of Science databases to retrieve the relevant studies and articles concerning ESG, corporate governance, and their interaction utilising the keyword (1. ESG 2. Board of Directors 3. Corporate Governance). The result unveiled the importance of ESG factors in influencing corporate strategies, policies, and the composition of boards as governing bodies. The final data findings consist of thirty papers identified through this review. The expected validation is comprised of the following three themes: (1) The significance of CG integration with ESG, (2) Framework for Research on ESG and CG, and (3) New research area on CG and ESG. The results highlight the necessity of incorporating CG on ESG principles as a foundation for a firm's sustainability and stakeholder trust. Furthermore, this assessment serves to identify gaps in knowledge, providing valuable insights for future research and policy implications.